1990
DOI: 10.1148/radiology.175.2.2326471
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial vascular lesions: optimization and clinical evaluation of three-dimensional time-of-flight MR angiography.

Abstract: The clinical value of three-dimensional time-of-flight magnetic resonance (MR) angiography was prospectively evaluated in 26 patients with congenital intracranial vascular lesions; 12 had arteriovenous malformations (AVMs), and 14 had venous angiomas. In the initial phase of the study the entire region of interest was imaged with one large acquisition volume (60-120-mm-thick slab). Later, the angiograms were obtained with adjacent but slightly overlapping, 30-mm-thick slabs, which clearly improved vascular det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(48 citation statements)
references
References 0 publications
0
47
0
1
Order By: Relevance
“…Measurements were taken with the neck in four different positions and with all grades of compression at the proximal and distal vertebral arteries and basilar artery levels. The accuracy of 20 phasecontrast [37][38][39] and 20 TOF sequences reliably correlated with conventional angiography [28,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were taken with the neck in four different positions and with all grades of compression at the proximal and distal vertebral arteries and basilar artery levels. The accuracy of 20 phasecontrast [37][38][39] and 20 TOF sequences reliably correlated with conventional angiography [28,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…6 ' 18 If this 3D MRA is combined with intravenous gadolinium, the difficulty with spin saturation (and intravascular signal loss) in the draining veins and distal nidus vessels is further reduced. 6 Regardless of the technique MRA cannot provide the physiologic information that can be derived from traditional catheter angiography such as the arteriovenous circulation time and arterial stump pressures. Edelman et al 23 -24 showed that it was possible to obtain some functional information with respect to identifying feeding vessels through the use of appropriately positioned saturation pulses.…”
Section: Vascular Malformationsmentioning
confidence: 99%
“…20,21 These spins are gradually saturated during movement within the slab. This saturation effect causes signal intensity loss in the peripheral arteries.…”
mentioning
confidence: 99%